2012
DOI: 10.1007/s12264-012-1283-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide pathway and the signal transduction network in neural development

Abstract: Abstract:The development of the nervous system is under the strict control of a number of signal transduction pathways, often interconnected. Among them, the phosphoinositide (PI) pathway and the related phospholipase C (PI-PLC) family of enzymes have been attracting much attention. Besides their well-known role in the regulation of intracellular calcium levels, PI-PLC enzymes interact with a number of molecules belonging to further signal transduction pathways, contributing to a specific and complex network i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 106 publications
(153 reference statements)
0
15
0
1
Order By: Relevance
“…Cholinergic nerve stimulation in basal forebrain and hippocampus was reported to be excitotoxic, causing tonic-clonic convulsions due to the release of glutamate mediated through the production of ROS (reactive oxygen species) [7]. The brain and nervous system are considered to be more susceptible to peroxidative damage than other tissues due to their high content of polyunsaturated lipid, high oxygen utilization and low antioxidative enzymes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cholinergic nerve stimulation in basal forebrain and hippocampus was reported to be excitotoxic, causing tonic-clonic convulsions due to the release of glutamate mediated through the production of ROS (reactive oxygen species) [7]. The brain and nervous system are considered to be more susceptible to peroxidative damage than other tissues due to their high content of polyunsaturated lipid, high oxygen utilization and low antioxidative enzymes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several Notch signaling pathway studies on neuronal development and neuronal degeneration have been reported [ 39 ]. The phosphatidylinositol signaling pathway is important in intra- and extra-cellular signaling and affects neuron development [ 40 ]. TOR signaling has also been reported as a key molecular pathway in nervous system development [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase of Ca 2+ moves PKC to translocate from cytoplasm to the cytoplasmic face of the plasma membrane [91]. Activated PKC enzymes phosphorylate specific serine or threonine residues on target proteins [91,96].…”
Section: Figurementioning
confidence: 99%